Cabaré da Santa: um projeto teatral luso-brasileiro, com Dagoberto Feliz e Jorge Louraço Figueira - Helderson Mariani (Revista Desassossego, 2020)
Interviews with the director Dagoberto Feliz and the playwright Jorge Louraço Figueira, about the 2008 theatrical project Cabaré da Santa, which has held with the Brazilian group Folias (São Paulo) and the Portuguese group Teatrão (Coimbra). The project occurred on the celebrations of the 100th anniversary of the Portuguese Royal Family’s arrival on Brazil.